DESAIN PEMBUATAN DAN UJI COBA KUMPARAN HELMHOLTZ BERBENTUK LINGKARAN - Ginisa Ardiyani; Erwin '; Salomo ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Design and study  of Helmholtz coils have been carried out.  The coils  diameter was designed of about    13 cm and  number of turns of    50, 100, 150, 200 and 250. Magnetic field that produced by those coils was measured using  pasco  magnetic probe PS-2162 as a function of an applied current, distances and number of turns. As comparison,  then the magnetic field produced by these coils had been compared to the standard one.  Maximum value of magnetic field was obtained at the center of the coil. For an applied current of 2 A, then the magnetic field at the center of the coils either  standard one  or the designed one  was  7.156 x 10-5T  and 5.907  x 10-5T respectively. The value of magnetic field increases as number of turns and current are increased, for the coils with number of turns of 50 and 250 that carrying current of 1.0 A  produced a magnetic field of  5.241 x 10-5T and 6.208 x 10-5T respectively. This is due to the direct relationship between current (I) and number of turns (N) against magnetic field as expected. The value of magnetic field decreases as moving away from the center of coil either in horizontal or vertical direction.